FAILURE MODES AND EFFECTS ANALYSIS (FMEA) ON TRACK INFRASTRUCTURE INTEGRITY ASSESSMENT - Angga Ahmad Maulana; Puja , IGN Wiratmaja; Wicaksono, Satrio (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Track infrastructure plays an important role in the railway business, where the safety of rail travel is determined by the integrity that exists in each component of the railway track. In this paper, an integrity assessment of track infrastructure is carried out using the Failure Modes and Effects Analysis (FMEA) method by identifying various failure modes for each component and track geometry that have existed in the field. Then a survey was conducted to track maintenance experts at PT Kereta Api Indonesia (Persero) to get the value of severity, occurrence, detection, and recommended actions taken. Based on the analysis, the failure mode with the highest Risk Priority Number (RPN) is the cracked rail on the welding/fish plate joint with a value of 280, while the failure mode with the lowest RPN is the loose rail with a value of 108. Then 21 failure modes fall into the